A Comparison of Colorimetric Assessment of Vaginal pH with Nugent Score for the Detection of Bacterial Vaginosis. (15th February 2017) - Hoffman, Matthew K.; Bellad, Mrutyunjaya B.; Charantimath, Umesh S.; Kavi, Avinash; Nagmoti, Jyoti M.; Nagmoti, Mahantesh B.; Mallapur, Ashalata A.; Katageri, Geetanjali M.; Ramadurg, Umesh Y.; Bannale, Sheshidhar G.; Revankar, Amit P.; Ganachari, M. S.; et al.
Abstract : Background . A Nugent score > 7 has been defined as the gold standard for the diagnosis for bacterial vaginosis (BV), though it is resource intensive and impractical as point of care testing. We sought to determine if colorimetric assessment of vaginal pH can accurately predict the occurrence of BV. Methods . We performed a planned subanalysis of 1, 216 pregnant women between 13 0/7 and 19 6/7 weeks who underwent vaginal examination as part of a randomized controlled trial. Using a standardized technique, specimens were obtained for colorimetric assessment and two separate slides for Gram staining. These slides were subsequently evaluated by two independent blinded microbiologists for Nugent scoring. Results . Interrater reliability of the interpretation of the Nugent score was excellent (intraclass correlation-individual 0.93 (95 CI 0.92 to 0.94) and average 0.96 (95% CI 0.95 to 0.97)). The sensitivity of an elevated pH > 5 for a Nugent score > 7 was 21.9% while the specificity was 84.5%. The positive predictive value in our population was 33.7% with a negative predictive value of 75.0%. Conclusion . Though the Nugent score is internally accurate, the prediction of BV using vaginal pH alone has poor sensitivity and specificity.